Frederico Pimentel Gomes e a estatística experimental no Brasil - Crisafuli, Erick de Paula (2015)
This work focuses on some aspects related to the context in which statistical researches developed by Frederico Pimentel Gomes (1921-2004) should be considered, regarding new elements arising from other documents and studies. It deepens some aspects concerning the application of statistic knowledge into Genetics, Agricultural Chemistry and Agronomy, addressing contextual framework. Gomes emphasized practical application of statistics to solve issues related to agricultural production. He points out the multifaceted role of statistic by establishing connections with different fields of knowledge. Specific analysis focused on original documents stresses the contextual framework of Gomes proposal which was managed in an interdisciplinary way, addressed to its practical application, without losing its theoretical counterpart